Characterization of Pathogenic Vibrio parahaemolyticus Isolated From Fish Aquaculture of the Southwest Coastal Area of Bangladesh - Siddique, Abu Baker; Moniruzzaman, M.; Ali, Sobur; Dewan, Md. Nayem; Islam, Mohammad Rafiqul; Islam, Md. Shafiqul; Amin, Mohammed Badrul; Mondal, Dinesh; Parvez, Anowar Khasru; Mahmud, Zahid Hayat (Frontiers in Microbiology, 2021)
Vibrio parahaemolyticus is a major foodborne pathogen responsible for significant economic losses in aquaculture and a threat to human health. Here, we explored the incidence, virulence potential and diversity of V. parahaemolyticus isolates from aquaculture farms in Bangladesh. We examined a total of 216 water, sediment, Oreochromis niloticus (Tilapia), Labeo rohita (Rui) and Penaeus monodon (Shrimp) samples from the aquaculture system where 60.2% (130/216) samples were positive for V. parahaemolyticus. Furthermore, we identified 323 V. parahaemolyticus strains isolates from contaminated samples, 17 of which were found positive for trh, a virulence gene. Four isolates out of the 17 obtained were able to accumulate fluid in the rabbit ileal loop assay. The correlation between the contamination of V. parahaemolyticus and environmental factors were determined by Pearson correlation. The temperature and salinity were significantly correlated (positive) with the incidence of V. parahaemolyticus. Most of the pathogenic isolates (94.1%) were found resistant to ampicillin and amoxicillin. O8: KUT was the predominant serotype of the potentially pathogenic isolates. ERIC-PCR reveals genetic variation and relatedness among the pathogenic isolates. Therefore, this region-specific study establishes the incidence of potential infection with V. parahaemolyticus from the consumption of Tilapia, Rui and Shrimp raised in farms in Satkhira, Bangladesh and the basis for developing strategies to reduce the risk for diseases and economic burden.